Impact of whole thorax irradiation on cardiac remodeling and outcome after ischemia/reperfusion. (3rd October 2022) - Mir, S; Wegener, K; Gorressen, S; Twarock, S; Haendeler, J; Altschmied, J; Sak, A; Stuschke, M; Jendrossek, V; Fischer, J W; Floegel, U; Grandoch, M
Abstract: Background: Thoracic irradiation is a fundamental treatment of several malignancies and has contributed to significant rise in long-term survival of cancer patients. However, a potentially increased risk of cardiac late effects, such as accelerated atherosclerosis, coronary heart disease or myocardial fibrosis, may partially diminish the therapeutic benefit and increase the risk of cardiovascular events, e.g. ischemia/reperfusion (I/R). The purpose of this project was to unravel the impact of whole thorax irradiation (WTI) on the outcome and cardiac remodeling after I/R. Method: 11-week-old male C57BL/6J mice were either exposed to WTI with a single dose (12.5 Gy) or sham-irradiation only (0 Gy) and subsequently observed over four weeks. Blood samples were taken to monitor early changes in circulating leukocytes (flow cytometry) and RNA was isolated from cardiac tissue to observe damage to mitochondria by analysis of different mitochondrial markers. To study the impact of WTI on cardiac remodeling and outcome after I/R, mice were subjected to ischemia by occlusion of the left anterior descending artery (for 45 minutes) four weeks after WTI or sham-irradiation, followed by reperfusion for up to three weeks. During early timepoints of cardiac remodeling, circulating immune cells and the immune cell influx in the heart were analysed (flow cytometry), ischemic area and cardiac inflammation were assessed by magnetic resonance imaging (MRI) and multiple cytokines were measured in the plasma (immunoassay). Results: After WTI, a downregulation of leukocyte numbers was observed three days after irradiation, which recovered over four weeks. In addition, WTI resulted in a decrease in relative mRNA expression of mitochondrial fission factor (MFF) and a decrease in relative ATP levels in irradiated mice, suggesting damage of cardiac mitochondria. The combined setup of WTI and I/R led to enhanced plasma concentration of IL-12(p70), IL-13, MCP-1 or MIP-1β and an increased ischemic area one day after I/R. Further, cardiac inflammation was increased three days post I/R in irradiated mice. Flow cytometric analysis revealed, increased amounts of circulating Ly6Chigh monocytes (% of all monocytes) and cardiac myeloid cells, specifically macrophages. Survival of irradiated mice was impaired already after one week post I/R; therefore, when analysing scar size three weeks later, no changes could be observed in the surviving mice. Conclusion: Our data show that WTI causes early damage to cardiac mitochondrial network. While WTI also led acutely to a decrease in circulating immune cells, upon I/R, the preexisting irradiation-induced cardiac damage impacts on circulating and cardiac macrophages and monocytes resulting in increased cardiac inflammation and plasma concentration of cytokines in irradiated mice. In sum, irradiation-induced cardiac damage and subsequently altered immune response are likely contributing to the impaired survival of irradiated mice after I/R. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): DFG - GRK 1739